Potensi Cuka Kayu dari Eucalyptus pellita dan Acacia mangium Wild Sebagai Antimikroba - Johan, Vonny Setiaries; ', Sudarnyoto; ', Rahmayuni (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Waste timber during logging Eucalyptus pellitaand Acacia mangium Wild from plant forest industry has not been in use, where it can processing as wood vinegar. The purposed of this study were to obtain wood vinegar from Eucalyptus pellita and Acacia mangium Wild and determine the antimicrobial activity from both wood vinegar. Antimicrobial activity conducted with view clear zone around the paper disc soaked in vinegar on a medium Nutrient Agarcontains microbial pathogens Staphylococcus aureus and Escherichia coli. Bothwoodvinegardilutedwithdistilled water at concentration of50%, 40%, 30%, 20% and10% respectively, andhad 3replicatesconcentration. The results showed that the yield of wood vinegar fromEucalyptus pellitais 32.89% and fromAcacia mangium Wild is 29.63%.Woodvinegarfrom Eucalyptuspellitaata concentration of 10% has azone ofinhibitionagainstStaphylococcus aureusaveragediameter3.38mmand50% at concentration 7.15mm, while theconcentration of10% inhibition zoneinthe bacteri Escherichiacolithe average diameter7.24mmand50% at concentration 8.79mm. Wood vinegar from all concentration indication has activity antimicrobial. Growth of Staphylococcus aureus and Escherichia coli was inhibited by both wood vinegar at concentration of 10%. Keywords: Wood Vinegar, Eucalyptus pellita, Acacia mangium Wild.